(untitled) (Research, Society and Development, 2025)
Polypharmacy, defined as the concomitant use of five or more medications, is a growing phenomenon, particularly among young adults with psychiatric conditions using antidepressants. This practice, driven by therapeutic guidelines and early diagnoses, is associated with a high risk of adverse drug interactions and significant side effects. Objective: To investigate the impacts of polypharmacy in young adults using antidepressants, focusing on drug interactions and clinical outcomes. Methodology: A systematic review was conducted following PRISMA guidelines. Searches were performed in PubMed, BVS, and Cochrane CENTRAL databases, covering the period from 2019 to 2024, focusing on the relationship between polypharmacy and antidepressant use in young adults. Results: Initially, 61 studies were identified, of which 12 met the inclusion criteria. Reported outcomes included: higher risk of cardiac arrhythmias, increased suicidal ideation and attempts, impaired antidepressant metabolism, hypoglycemia, falls, mortality, gastrointestinal events, reduced treatment adherence, and increased incidence of diabetes mellitus. Women and individuals from lower socioeconomic classes exhibited a higher prevalence of polypharmacy. Conclusion: Polypharmacy among young adults using antidepressants is associated with a range of adverse outcomes, compromising therapeutic efficacy and patient safety. The importance of rigorous monitoring, individualized treatment, and detailed investigation of drug interactions by healthcare professionals is emphasized.